Effect of Materials For Interim Restoration on Estimation of Working Length Using Electronic Apex Locator: in vitro Study - Ortega,F (Universidad de La Frontera. Facultad de Medicina, 2021)
ABSTRACT: The aim of this in vitro study was to evaluate measurement accordance using an electronic apex locator for estimation of working length in endodontics when different restorative materials for interim crown restoration are utilized. For this study, 13 single-rooted premolars with endodontic occlusal access cavity were prepared. To establish the working length of each tooth, these were mounted in alginate and with the help of an electronic foramen locator and endodontic file K-file # 15, the working length was established. This length was later compared to the estimated working lengths using different intermediate restoration materials. These materials were: Superior Chemfil, Ketac ™ Molar Easymix and Filtek z350 resin. In the electronic measurements, an acceptable tolerance range of variation up to ± 0.5 mm was considered. Highest discrepancies were considered erroneous. For these measurements, central tendency and dispersion were analyzed. The Bland-Altman method was used, and the ANOVA test with a significance level of p <0,05 for statistic difference. Regarding measurements' acceptability and the type of interim restoration material utilized, 7 were acceptable, and 6 were unacceptable for ChemFil Superior, 12 were acceptable and 1 unacceptable for Ketac™ Molar Easymix, and 11 were acceptable and 2 were unacceptable for Filtek Z350 composite resin. The average difference between all electronic measurements was 0.29 (± 0.44). Chemfill Superior showed the most prominent variation between measurements 0.58 (± 0.45). When using an electronic apex locator, measurements showed statistically significant differences depending on the interim restoration material of choice (p<0.05). In conclusion, the measurement accordance using electronic apex locator to estimation the working length is higher, however the electronic estimation of working length can be significatively affected by the material chosen for interim temporary restoration.